Neutrosophic e-open Sets in a Neutrosophic Topological Spaces - Thangaraja P; vadivel A; Bobin A; Thayalan S; John Sundar C; John Sundar C (Neutrosophic Sets and Systems)
This study presents the concept of a neutrosophic e-open set, defined as the union of neutrosophic δP-open sets and δS-open sets within the framework of neutrosophic topological spaces. It also explores near open sets, highlighting their characteristics and providing illustrative examples of neutrosophic e-open sets. Furthermore, we examine fundamental properties and offer examples related to the neutrosophic e-interior and e-closure. In addition, we demonstrate the application of the neutrosophic score function and its negative counterpart in solving a mobile phone selection problem. This is achieved by utilizing neutrosophic topological spaces structured around various attributes and alternatives, ultimately determining score values to support decision-making.